The New Type of Employment: the Specificity of the Platform Economy and Platform Work - Arany, László; Popovics, Péter András (International Journal of Engineering and Management Sciences, 2024)
The industry value of the global platform economy exceeded 7 trillion US dollars by the end of the second decade of the 21st century. The income generated by the platform economy in the European Union produced an almost five-fold increase in the period between 2016-2020, as its volume increased from 3 billion euros to 14 billion euros. Nevertheless, due to the lack of global consensus and precedent, the delimitation of the platform business model and work, its legal regulation and verifiability and compliance, due to its innovative nature, are unresolved at the world and European level. The objective of the article is to define the conditions, rules and practical application of the platform economy and platform work, relying on international (English-language, mostly European) secondary information, thereby revealing the problems and difficulties, as well as discussing its advantages and disadvantages.